COMPARATIVE STUDY OF THE TWO MEASURING SIGNALS IN THE CORRELATION IDENTIFICATION SYSTEM - Rybalka, R. V.; Havryliuk, V. I.; Bezrukov, V. V. (Science and Transport Progress, 2008)
On the basis of the developed imitating model and realized modeling it is shown that at both noise absence and presence a signal of kind of sine divided on its own argument has no advantages above a signal of delta function kind in the system characteristic measurement system by correlation method of identification.